1997
DOI: 10.1042/cs0920385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Dose Chemotherapy on Intestinal Permeability in Humans

Abstract: 1. Mucositis is a common side-effect of chemotherapy which is difficult to assess except by invasive means such as upper gastrointestinal endoscopy. Differential absorption of mono- and di-saccharides, such as rhamnose and lactulose, is a non-invasive measure of intestinal damage. 2. The purpose of the study was to assess the duration and severity of intestinal damage in patients undergoing high-dose chemotherapy and autologous blood stem-cell transplantation for malignant disease. 3. Thirty-five patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 10 publications
2
120
0
Order By: Relevance
“…Absorption is increased after only 2 days treatment with chemotherapy 76 suggesting that cytokines might interfere with the tight junctions (see inflammatory phase) rather than directly inhibiting cell proliferation, which tends to occur later. 77 Altered permeability continues to progress until reaching a peak about 7 days after conditioning therapy has been completed 78 and returns to normal about 4 weeks later. 79 This mirrors the oral MBI and neutropenia (Figure 1).…”
Section: Sugar Absorption Testsmentioning
confidence: 99%
“…Absorption is increased after only 2 days treatment with chemotherapy 76 suggesting that cytokines might interfere with the tight junctions (see inflammatory phase) rather than directly inhibiting cell proliferation, which tends to occur later. 77 Altered permeability continues to progress until reaching a peak about 7 days after conditioning therapy has been completed 78 and returns to normal about 4 weeks later. 79 This mirrors the oral MBI and neutropenia (Figure 1).…”
Section: Sugar Absorption Testsmentioning
confidence: 99%
“…10 In 1997, Keefe et al identified a transient abnormality in intestinal permeability in patients receiving high-dose chemotherapy. 23 Marked abnormalities in intestinal permeability have also been shown in patients receiving various myeloablative treatments 24 indicating that intestinal function is compromized by various cytotoxic regimens. Further, morphological defects in tight junctions have been identified, with Keefe et al (2000) demonstrating significant increases in the number of open intestinal tight junctions in patients receiving high-dose chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Malabsorption is generally attributed to the consequences of oncologic treatments reducing the gastrointestinal absorption. Chemotherapy is, in part, responsible for the intestinal alterations [9,10]. In the case of CHF, the illness leads to increased sympathetic activity, which contributes to a redistribution of blood flow away from the splanchnic circulation.…”
Section: Altered Intestinal Absorption Of Nutrientsmentioning
confidence: 99%